Humanizing Islamic Education in Elementary Islamic School: Teacher Strategies, Classroom Dynamics, and Contextual Factors at MIM Pringkuku - Julyana Asokawati; Ahmadi (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study investigates the humanization of Islamic Education (PAI) learning at MIM Pringkuku, Pacitan, focusing on humanistic value implementation, teacher strategies, and supporting-inhibiting factors. A qualitative descriptive case study design was employed, with data collected through structured observation, semi-structured interviews with the Islamic Education teacher, school principal, and nine sixth-grade students, and documentation study. Data were analyzed using the Miles, Huberman & & Saldaña interactive model with triangulation to ensure validity. Findings reveal that humanistic values are consistently embedded through warm classroom atmosphere creation, empathic responses to student mistakes, and organic moral value internalization across all Islamic Education subjects. Teacher strategies include contextual learning, dialogic teaching, and a peer tutoring system that achieved most of students completing Juz 30 memorization. Supporting factors are ecosystemic, encompassing teacher commitment, institutional support, and community involvement, while the primary challenge is the cognitive-affective gap between high in-school mastery and inconsistent value implementation in students' daily lives. This study proposes that the single-teacher condition creates a consistent humanistic pedagogical identity across all Islamic Education subjects, reframing Islamic Education humanization as an ecosystemic rather than individual phenomenon.